PENERAPAN RAPID APLICATION DEVELOPMENT MELALUI SISTEM INFORMASI GEOGRAFIS UNTUK PEMETAAN LEMBAGA PENDIDIKAN ANAK USIA DINI - Andi Setiawan; Ade Irma Purnamasari; Nana Suarna (Infotekmesin, 2019)
The growing and development of early childhood education institutions in Cirebon Regency, requires a very accurate location data collection so that information can be quickly accessed and presented. Accurate location data collection can be presented through an information system presentation mechanism from several stages in the system modeling process. System modeling must emphasize a very short development cycle that is needed during system development. This study emphasizes the modeling of the Rapid Application Development system, so that the information system for PAUD location data collection in Cirebon Regency can be produced quickly and accurately in less than 30 working days. Some of the stages developed in this study include business modeling, data modeling, process modeling, and ending with application implementation. The expected result of this research is that the system can help provide information on the location of early childhood education institutions in Cirebon Regency as much as 84,390%, while the quality of information produced is 85,366%, and the response to the system that can be accepted by the community is 84,390%.